Budaya Organisasi Memoderasi Hubungan Penganggaran Partisipatif Terhadap Kinerja Managerial (Studi Pada Pemerintah Kabupaten Halmahera Timur) - Iwan S. Seber; Burhan Zakaria (Akuntabilitas, 2021)
This study examines the effect of participatory budgeting on managerial performance with organizational culture as moderating variable. Proportional random sampling is technique used in this study. There were 135 state civil servant within the regional apparatus organization in the East Halmahera Regency as respondents in this study. The results of statistical test show that the organizational culture weakens relationship between participatory budgeting and managerial performance. Partially, participatory budgeting has an effect on managerial performance. The implication of this research is that it can be used by regional apparatus organizations to design budget planning arrangements in the East Halmahera Regency.